Surgical Management of Retro-Odontoid Cystic Mass with Cervicomedullary Compression. (20th May 2021) - Lyons, Mark K.; Neal, Matthew T.; Kalani, Maziyar; Patel, Naresh P.
Abstract : Retro-odontoid cysts are a rare cause of cervicomedullary compression. The etiology of these lesions is not completely understood. Previous trauma and instability at the cervicomedullary junction may be the precipitating event in the development of retro-odontoid cysts in rare cases. We discussed the neurosurgical evaluation of a patient who presented with progressive and rapid neurological deterioration secondary to cervicomedullary compression. Posterior occipitocervical fusion was performed. The patient made an excellent neurological recovery, and postoperative imaging studies demonstrated resolution of the compression and intramedullary cyst.